2016
DOI: 10.1021/jacs.6b01202
|View full text |Cite
|
Sign up to set email alerts
|

Internal Activation of Peptidyl Prolyl Thioesters in Native Chemical Ligation

Abstract: Prolyl thioesters have shown significantly lower reactivities in native chemical ligation (NCL) in comparison to that of the alanyl thioester. This report describes a mild and efficient internal activation protocol of peptidyl prolyl thioesters in NCL without using any thiol-based additives, where the introduction of a 4-mercaptan substituent on the C-terminal proline significantly improves the reactivity of prolyl thioesters via the formation of a bicyclic thiolactone intermediate. The kinetic data indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 106 publications
0
45
0
Order By: Relevance
“…Fmoc-SPPS using photoprotected a-ketoacid building blocks (a) and analytical HPLC traces (220 nm) of crude (c and e) and purified (b and d) peptide segments with photoprotected a-ketoacids. In NEDD8 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) 17 (b and c), the two diastereoisomeric peptides resulting from the racemic protecting group rac-2 elute as separate peaks.…”
Section: Fmoc-spps Of Photoprotected C-terminal Peptide A-ketoacidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fmoc-SPPS using photoprotected a-ketoacid building blocks (a) and analytical HPLC traces (220 nm) of crude (c and e) and purified (b and d) peptide segments with photoprotected a-ketoacids. In NEDD8 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) 17 (b and c), the two diastereoisomeric peptides resulting from the racemic protecting group rac-2 elute as separate peaks.…”
Section: Fmoc-spps Of Photoprotected C-terminal Peptide A-ketoacidsmentioning
confidence: 99%
“…All peptides were prepared by standard Fmoc-SPPS. NEDD8 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) 25 was prepared from protected isoleucine a-ketoacid and assembled until Thr7 after which Fmoc deprotection appeared to be difficult. From this point on, the deprotection was achieved using 20% piperidine in DMF with 3% of DBU, preceded by a LiCl (0.8M in DMF) wash. Two variants of the NEDD8 segments were prepared, one (18) with the photoprotected tyrosine a-ketoacid and (S)-Boc-5-oxaproline, and the other one (30) with a tyrosine a-ketoacid and photoprotected (S)-5-oxaproline.…”
Section: Convergent and One-pot Ligations Of Nedd8mentioning
confidence: 99%
See 1 more Smart Citation
“…[17] Dong et al have also reported NCL via a bicyclic thiolactone intermediate generated from prolyl thioesters. [18] However, the use of γ-thiolactone in peptide synthesis had been limited to those early aminolysis examples by glycine and glycylglycine. [10] The fact that large excess of amine was required to achieve moderate yields is not practical for peptide synthesis since one segment of a peptide could be valuable or only available in small amount.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the search for more effective and practical additives, 15 studies have also been conducted exploiting the presence of –SH functionalities within the peptide segments to activate the C-termini under thiol additive-free conditions, 16 including a recent report from our group on a 4-thioproline-based ligation at the Pro-Xaa sites. 17 In contrast to the internal activation originating from the cysteine residues within the sequence, a constrained thiolactone structure was suggested to be crucial in accounting for the drastically increased reactivity in comparison to the regular prolyl thioesters. 18 Despite these improvements, methods that can improve efficiencies at other sterically demanding sites under mild reaction conditions are still of great importance, and call for further investigations.…”
Section: Introductionmentioning
confidence: 99%